Happiness Management: A Culture to Explore From Brand Orientation as a Sign of Responsible and Sustainable Production - Ravina-Ripoll, Rafael; Nunez-Barriopedro, Estela; Almorza-Gomar, David; Tobar-Pesantez, Luis-Bayardo (Frontiers in Psychology, 2021)
The overarching call to action represented by the Sustainable Development Goals (S.D.G.s) calls for new models of sustainable production and management. Likewise, in periods of crisis such as the current COVID19 pandemic, companies are forced to develop competitive and sustainable development strategies to increase their brand value and achieve a good market position. Therefore, this work's main objective is to design a model (S.E.M.) to analyse the main critical dimensions of brand orientation to influence happiness in responsible and sustainable entities. For this purpose, a descriptive cross-sectional study was carried out based on primary data from a survey of a representative sample of 216 managers of small and medium-sized enterprises in Andalusia (Spain) in the construction, industry, and services sectors. The model results reveal that they are significant dimensions of brand orientation and positively direct influence on happiness management. One of the significant managerial implications of this work is that the model allows for more responsible and sustainable management of entities by considering brand orientation about happiness.